(untitled) (REGE Revista de Gestão, 2023)
Purpose – The study aims to investigate urban agriculture in the city of S ao Paulo from the perspective ofsocial capital. The specific objectives are (1) to identify the effects of social capital on urban agriculture and (2)to investigate social capital formation (its sources and challenges imposed onto its development).Design/methodology/approach – Initially, a review of the literature was carried out in order to understandthe main concepts used in the field of study. Semi-structured interviews were also carried out with people fromurban agriculture initiatives, and they were analyzed under the lens of social capital.Findings – Aspects of social capital were recognized and organized in a framework including sources, effectsand challenges. The first deals with consummatory or instrumental sources that generate social capital. Thesecond deals with the following effects: generation of human capital, citizenship, engagement, access andmobilization of resources, and access to information. The third deals with the challenges to its formation relatedto homophily and the perception of benefits from this form of capital.Originality/value – Urban agriculture plays an increasingly important role in relieving the pressuregenerated by the food production system, being part of the solution to food security and sustainability issues.Many researchers recognize important social aspects acting on the dynamics of the movement and the effects ofactivities on the generation of social capital. The contribution of this work is to deepen the understanding of thistype of capital in the context of urban agriculture.